Quality of life of elderly persons in Manaus measured by the Flanagan Scale - Figueiredo Neto, Esmeraldino Monteiro De; Corrente, José Eduardo (Universidade do Estado do Rio Janeiro, 2018)
AbstractObjective:the aim of the present study was to evaluate the quality of life of elderly people enrolled in specialized elderly care centers in Manaus and compare the findings with the results of already published studies.Method:a cross-sectional study was conducted with 741 elderly people enrolled in three of the centers in the city, from November 2015 to March 2017 using a socioeconomic and demographic questionnaire and the Flanagan Quality of Life Scale (FQLS). Interviews were carried out by previously trained physiotherapy students of the Federal University of Amazonas.Results:the majority of the elderly were female, with a mean age of 69±6.6 years, married, retired but still working, with a low income and low educational level. When they assessed their quality of life, however, they appeared satisfied. When compared to populations in other countries and regions of Brazil, despite their low socioeconomic profile, they demonstrated a higher quality of life than populations of developed countries. Some domains of the scale were inverted in relation to the original scale.Conclusion:the results allow us to conclude that even elderly persons with low socioeconomic status are satisfied with their quality of life.

ResumoObjetivo:o objetivo do estudo foi avaliar a qualidade de vida de idosos atendidos nos Centros de Atenção Integral a Melhor Idade (CAIMI) do município de Manaus.Método:trata-se de um estudo observacional, transversal, com 741 idosos, utilizando um questionário socioeconômico e demográfico e a Escala de Qualidade de Vida de Flanagan (EQVF).Resultados:a maioria dos idosos era do sexo feminino, com média de idade de 69 (±6,6) anos, casados, aposentados, porém, ainda trabalhavam, com baixa renda e baixa escolaridade, mas que, quando avaliada a qualidade de vida, os mesmos mostravam-se satisfeitos. Quando comparados com populações de outros países e regiões do Brasil, mesmo com um baixo perfil socioeconômico, mostraram uma melhor satisfação com a qualidade de vida que populações de países desenvolvidos. Alguns domínios da escala de qualidade de vida foram invertidos em frente à escala original.Conclusão:mesmo os idosos apresentando baixo nível socioeconômico, encontram-se satisfeitos com sua qualidade de vida.
Qualidade de vida dos idosos de Manaus segundo a escala de Flanagan
Keywords: Quality of Life; Elderly; Aging; Qualidade de Vida; Idoso; Envelhecimento